Adolescents and the dark side of social media—Law enforcement perspectives - Äijälä, Juho; Riikonen, Reetta; Huhtinen, Aki-Mauri; Sederholm, Teija (Frontiers in Communication, 2023)
Adolescents are the most active user group of social media sites. The malicious use of social media and the adverse effects it can have on both societal and individual well-being are well documented. Adolescents are the most active user group of social media sites. Due to being in a phase of both biological and psychological development, they may be particularly vulnerable to the darker sideaspects of social media, such as its illegal aspects or coordinated information influencing.. With this research, we aimed to identify threats Finnish adolescents face on social media from a lawenforcement perspectiveand their effect on both individual and societal well-being. To reach this goal, we performed semi-structured interviews with police officers from Finnish preventive measures police units. To identify and structure threats that adolescents face, we employed a twofold analysis. In the first part, we conducted inductive content analysis, which revealed three primary threats: polarisation, disinformation, and social media as a pathway to illegal activities. In the second part, we employed the Honeycomb-model of social media functionality as a classificatory device for structuring these threats. Our findings provide explorative insights into the threats social media might presents to adolescents from the point of view of the Finnish law-enforcement system.Polarisation in social media was considered to generate an unhealthy environment for adolescent interactions. Coordinated disinformation was found to easily spread among adolescents, and social media was understood to provide a pathway to illegal activities even to adolescents who would not otherwise engage in criminal behaviour. In the second stage of the analysis, we employed the Honeycomb model of social media functionality as a tool for theory-driven analysis and broke down the identified threats into 'threat profiles'. Our theory-driven analysis revealed more nuanced descriptions of how these threats are present on social media.